The Impact of Export Activity, Location, Size and Supply Chain Management on Firm’s Performance - Mustika Dewi, Erfinda; Fanani, Sunan (International Journal of Supply Chain Management, 2020)
The foremost purpose of the current study is to examine the impact of export activities along with location, size and supply chain management impact on the firm performance of the pawnshop situated in Jember, Indonesia. The data has been gathered from the employees of pawnshop situated in Jember, Indonesia by using questionnaires while PLS-SEM has been executed for analysis purpose. The results indicated that export activities, location, size and supply chain management have positive along with the significant impact on the firm performance of the pawnshop situated in Jember, Indonesia. These findings are valuable for the new researchers while investigating this area in future along with the policymakers who want to develop the policies related to the supply chain and firm performance.